Mining the Roles of Wheat (Triticum aestivum) SnRK Genes in Biotic and Abiotic Responses - Jiang, Baihui; Liu, Yike; Niu, Hongli; He, Yiqin; Ma, Dongfang; Li, Yan (Frontiers in Plant Science, 2022)
Sucrose non-fermenting-1-related protein kinases (SnRKs) play vital roles in plant growth and stress responses. However, little is known about the SnRK functions in wheat. In this study, 149 TaSnRKs (wheat SnRKs) were identified and were divided into three subfamilies. A combination of public transcriptome data and real-time reverse transcription-polymerase chain reaction (qRT-PCR) analysis revealed the distinct expression patterns of TaSnRKs under various abiotic and biotic stresses. TaSnRK2.4-B, a member of SnRK2s, has different expression patterns under polyethylene glycol (PEG), sodium chloride (NaCl) treatment, and high concentrations of abscisic acid (ABA) application. Yeast two-hybrid assay indicated that TaSnRK2.4-B could interact with the SnRK2-interacting calcium sensor (SCS) in wheat and play a role in the ABA-dependent pathway. Moreover, TaSnRK2.4-B might be a negative regulator in wheat against pathogen infection. The present study provides valuable information for understanding the functions of the TaSnRK family and provides recommendations for future genetic improvement in wheat stress resistance.